On Some Challenges for Ethics Committees: Brief Concluding Remarks on the Sidelines of the Conference “Ethics Committees: A Bridge Between Care, Research, and Rights” (Trento, May 8, 2025) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The paper analyses the role of ethics committees as an essential hub between scientific research, clinical practice and the protection of fundamental rights, starting from the themes that emerged in the conference “Ethics Committees: A Bridge Between Care, Research and Rights” (Trento, May 8, 2025). After a summary of the main contributions, the focus is on the current challenges facing ethics committees for clinical trials and clinical ethics, particularly in relation to the digitalization of biomedical research, the use of artificial intelligence systems and healthcare big data, as well as the European regulatory framework. The essay also examines the role of clinical ethics committees in end-of-life decisions and procedures for accessing medically assisted suicide assistance, in light of constitutional jurisprudence and ongoing legislative debate, highlighting their role as a safeguard against vulnerable individuals. In conclusion, we emphasize the centrality of ethics committees as independent and multidisciplinary bodies, called upon to act as a bridge between scientific innovation, ethical responsibility, and the protection of human dignity.
Keywords: ethics committees; artificial intelligence; clinical trial; end-of-life